THE CAPTURE FISHERY OF RIVER GANGA AT BUXAR (BIHAR, INDIA) IN THE YEARS 1952-54 - Jhingran, V G (Indian Journal of Fisheries, 2015)
Records of catch statistics of any fishery are vital for its judicious, exploitation and development. There are many difficulties in the way of collection of such statistics relating to the capture fisheries of the Indian rivers, such as the very diffuse and scattered nature of the industry, lack of fixed landing grounds and hours of landing and very diverse trade practices.* Since up to the present day, except for the data given in the Marketing Series No. 65 (1951) on certain aspects of inland fisheries, no information is available on the species and size composition of riverine fish catches and their relative seasonal abundance, an attempt has been made to study these aspects of commercial fish landings at Buxar, and the results of the studies conducted are presented in this paper. Buxar was chosen as a site for study firstly because it is an important landing centre of gangetic fish and the landings here appear to be generally representative of a long stretch of gangetic belt in Eastern India.